2016
DOI: 10.1111/1756-185x.12913
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ agonist rosiglitazone inhibits migration and invasion by downregulating Cyr61 in rheumatoid arthritis fibroblast‐like synoviocytes

Abstract: Our results demonstrate for the first time that PPARγ agonists may have beneficial effects on the migration and invasion of RA-FLS via the downregulation of Cyr61. Therefore, PPARγ agonists could be potential treatment targets for RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Once CB2R is stimulated by BCP, other pathways are activated such as SIRT-1/PGC-1α and AMPK/CREB [19], therefore BCP may exert its anti-inflammatory activity thanks to PPAR-γ activation following CB2R stimulation. Interestingly, PPAR-γ also exerts an important role in rheumatoid arthritis [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Once CB2R is stimulated by BCP, other pathways are activated such as SIRT-1/PGC-1α and AMPK/CREB [19], therefore BCP may exert its anti-inflammatory activity thanks to PPAR-γ activation following CB2R stimulation. Interestingly, PPAR-γ also exerts an important role in rheumatoid arthritis [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Cyr61, a very important cell matrix adjustment factor, has been found to play an important role in regulating cell adhesion 11 , migration 12 , proliferation 13 , angiogenesis 14 , inflammation 15 and tissue reconstruction 16 . In our transcriptomics study, Cyr61 was identified as one of the most significantly differential genes in choroid tissue of diabetic mice (data not shown).…”
Section: Introductionmentioning
confidence: 99%
“…Blocking the interaction of CD63 with its endogenous ligand TIMP1 34 might be exploited to deplete FLC stem cell populations by disrupting stem cell maintenance mechanisms. 36 Drugs that inhibit YAP1, 37,45 AREG, 46,47 CTGF, 30,31 and/or cysteine-rich angiogenic inducer 61 (CYR61) 48,49 could be engineered to bind to CD63, thereby targeting their delivery to FLC cells to reduce tumor growth, metastasis, and desmoplasia. Finally, MSLN has been successfully targeted by CAR-T cells and other immunotherapies in ovarian cancer, 50e52 suggesting another novel, and more personalized, therapeutic strategy that might be applied to FLC.…”
Section: Discussionmentioning
confidence: 99%